Uma solução de reconfiguração leve para Paxos - Paula, Anderson Parra de (2015)
Paxos is an active replication algorithm that keeps the same shared state consistently among servers that handle requests from an application. It is unusual to find applications where the main processing happens through a replication algorithm such as Paxos, mostly due to the high number of exchanged messages required to keep the state consistent. This restricts the system scalability to a handful of replicas. To increase the applicability of active replication, we would like be able to not only make the capacity of processing proportional to the number of servers employed, but also change dynamically the number of server according to demand. In this dissertation we explored reconfiguration on systems that use active replication. We proposed two mechanisms: (1) efficient protocolo for state transfer; and (2) incorporation of new replicas in the system with no significant increase in the cost to keep the whole system consistent. Our approach uses both mechanisms to create reader replicas, capable of answering all application requests without taking an active part in the costly operations of the Paxos algorithm.